PENGARUH CURRENT RATIO, RETURN ON ASSET, RISIKO BISNIS, UKURAN PERUSAHAAN, DAN PAJAK TERHADAP STRUKTUR MODAL - HALLY INNAYAH SUNGKAR; TITA DEITIANA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to test and analyze empirically the influence of current ratio, return on asset, business risk, firm size and tax to capital structure which proximate by debt to equity ratio, and compare the result from previous research within this research. Data used in this research is from annual financial statements for mining sector industry, which listed in Indonesia Stock Exchange (IDX) period 2008 – 2015. The purposive sampling is used as sampling technique, where 6 companies met the criteria and were analyzed using panel data regression with fixed effect model to test the hypothesis. The result of this research shows that current ratio, return on asset, business risk, firm size and tax do not influence capital structure.